Review Of Temporary Modifications To The Fund's Access Limits In Response To The Covid-19 Pandemic. (Policy Papers; Policy Paper, 2021)
Over the course of the pandemic, the Fund has made several modifications to the access limits on the use of Fund's resources to increase the borrowing space under the hard caps on emergency financing and under the annual limits that trigger exceptional access (EA) safeguards under GRA and PRGT. The current temporarily-increased access limits expire at end-December 2021, and absent policy changes, the limits would return to the lower pre-pandemic levels or to the new PRGT annual access limit. Staff proposes to let all access limits return to pre-pandemic levels (or the new PRGT annual access limit), with the exception of the cumulative access limits for emergency financing instruments, which would be extended at the current level for another 18 months.